2011
DOI: 10.1007/s00134-011-2212-6
|View full text |Cite
|
Sign up to set email alerts
|

High-dose selenium reduces ventilator-associated pneumonia and illness severity in critically ill patients with systemic inflammation

Abstract: Daily infusion of 1,600 μg Se (as selenite), following an initial bolus of 2,000 μg, is novel and without short-term adverse events. High-dose parenteral selenite significantly increases Se status, improves illness severity, and lowers incidence of hospital-acquired pneumonia including early VAP for SIRS patients in ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 36 publications
4
100
1
Order By: Relevance
“…There are studies performed with selenium in infectious complications in critically ill patients (56,57). In a study, high-dose selenium treatment was shown to reduce the incidence of ventilator-associated pneumonia (56).…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies performed with selenium in infectious complications in critically ill patients (56,57). In a study, high-dose selenium treatment was shown to reduce the incidence of ventilator-associated pneumonia (56).…”
Section: Antioxidantsmentioning
confidence: 99%
“…In a study, high-dose selenium treatment was shown to reduce the incidence of ventilator-associated pneumonia (56). In the study by Andrews et al in critically ill patients, adding selenium to parenteral nutritional solutions was reported to reduce the development of new infections (57).…”
Section: Antioxidantsmentioning
confidence: 99%
“…In certain patient populations, reduced plasma selenium levels have been associated with increased morbidity and mortality, 13,128,174 therefore it may be prudent to further assess plasma selenium levels in transfusion-dependent and massively transfused patients and if indicated, to consider supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the critically ill suggest that selenium should be administered prior to injury, as giving it after injury seems to have little effect on oxidative injury. 128 Given that the onset of injury in cardiac surgical patients is predictable (initiation of CPB plus removal of aortic cross clamp) the cardiac surgical patient may be the ideal patient to benefit from selenium supplementation. However, to understand which patients may potentially benefit from supplementation it is first important to know (i) background levels in the local healthy population, (ii) what are the clinical consequences of low selenium levels.…”
Section: Intra-operative Influencesmentioning
confidence: 99%
See 1 more Smart Citation